PAIR for Hepatic Hydatid Cyst: A study in tertiary care hospital in Nepal - Lohani, B; Gurung, G; paudel, S (Journal of Institute of Medicine Nepal, 2013)
Introduction: The purpose of this study was to assess the outcome of PAIR in patients with hepatic hydatid cysts. Methods: A total of 17 hepatic hydatid cysts were treated by PAIR in a tertiary care teaching hospital in Nepal from June 2007- May 2009. In all cases, local anesthesia was applied. All the patients were kept in supine except 1 where the patient was kept in left lateral position due to location of the cyst. A spinal needle of 18G was used to puncture the cyst. A connecting tube was attached at the hub of the needle to facilitate the aspiration & to prevent the accidental dislodgement of the needle. 95% alcohol was used as scolecidal agent in 12 cysts & 20% hypertonic saline in 5 cysts. The process was repeated in when the aspirated fluid was > 100 ml. Results: A total of 17 hydatid cysts of liver were treated with PAIR under ultrasound guidance. The age of the patient ranged from 10-76 years. All patients had signs & symptoms of a hepatic mass caused by the cysts. All the cysts had prominent fluid component which was anechoic or hypoechoic with marked enhancement of back wall echoes on USG. A few patients had CT scans owing to the location of the cysts. Majority of the cysts were in right lobe (12) & rest were in the left lobe (5, one patient had two cysts). The maximum amount of fluid aspirated was 1000 ml. The volume of alcohol / hypertonic saline was 1/3rd of the aspirated fluid. No major complication was found in any of the patients. Following aspiration all the patients were relieved of their symptoms. Follow up ultrasonogram showed decrease in diameter of the cyst. Conclusion: Among the treatment modalities of hydatid disease though surgery is the first choice treatment, it is associated with considerable morbidity. Chemotherapy with benzimidazoles carbamates is palliative as it is poorly absorbed by the intestine & is unable to diffuse across the cyst wall. PAIR has the benefits of minimal invasiveness, less morbidity & hospital stay as compared to surgery along with confirmation of diagnosis (parasitological examination of the fluid) and cost-effectiveness among others.